The Effect of Profitability and Leverage on Tax Avoidance with Corporate Social Responsibility as a Moderation Variable - Yoga Aditya; Moh Yudi Mahadianto; Mardi Mardi (Asian Journal of Management Analytics, 2026)
This study aims to examine the Influence of Profitability (ROA) and Leverage (DAR) on Tax Avoidance (ETR) with Corporate Social Responsibility (CSR) as a moderation variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 – 2024. The research uses a Quantitative approach. With the purpove sampling technique, 36 samples from 91 companies were produced. Data analysis using panel data regression using EViews 12 SV software. The results show that profitability has a positive and significant effect on ETR, which means that the higher the profitability, the lower the tax avoidance rate. Meanwhile, Leverage has a negative but insignificant effect on ETR. CSR has been proven to be able to moderate the relationship between profitability and leverage to tax avoidance by weakening and strengthening the influence of each variable.